tVNS alters inflammatory response in adult VPA‐induced mouse model of autism: evidence for sexual dimorphism - Hale Gök Dağıdır; Neslihan Bukan; Meltem Bahcelioglu; Ayşen Çalıkuşu; Ece Alim; Saadet Özen Dizakar; Elif Topa; Hayrunnisa Bolay (FEBS Open Bio)
Autism is a neurodevelopmental disorder with limited treatment alternatives and which incidence is increasing. Some research suggests that vagus nerve simulation might lead to the reduction of certain symptom. Therefore, we aimed to examine the effect of bilateral transcutaneous auricular vagus nerve stimulation (tVNS) on the inflammatory response in an adult valproic acid (VPA) induced mouse (C57BL6) model of autism for the first time. The autism model was induced by oral VPA administration (600 mg·kg−1) to C57BL/6 pregnant mice on E12.5 days. The study included three groups: the VPA Transcutaneous Auricular Stimulation Group (VPA + tVNS), the VPA Control Group (VPA + sham), and the Healthy Control Group (Control + sham). Each group included 16 mice (8 M/8 F). Our results show that serum IL‐1β and IL‐6 levels were significantly higher in male VPA‐exposed mice than controls. However, IL‐1β was significantly lower, and IL‐6, TNF‐ α, and IL‐22 were not different in female VPA‐exposed mice compared to the control group. Brain NLRP3 levels were significantly higher in both sexes in the VPA autism model (P < 0.05). tVNS application increased brain NLRP3 levels in both sexes and reduced serum IL‐1β levels in male mice. We conclude that cytokine dysregulation is associated with the VPA‐induced adult autism model, and the inflammatory response is more pronounced in male mice. tVNS application altered the inflammatory response and increased brain NLPR3 levels in both sexes. Further studies are needed to understand the beneficial or detrimental role of the inflammatory response in autism and its sexual dimorphism.